Strukturwandlungen in der Agrarwirtschaft im Tal von Tehuacán/Pue. - Mexiko - Seele, Enno (ERDKUNDE, 1986)
The rapidly advancing urbanization process, above all in the Valley of Mexico-City, requires an increased production of animal protein in Mexican farming. The innovation of new technologies and industrial production methods resulted in a spatial concentration in farming, especially in the industria avicola, the Mexican poultry industry. The agricultural structure in the Valley of Tehuacan has been particularly influenced by this subsector of agro business industry. The development in this area has (since 1947) been determined, above all, by the initiatives and innovations introduced by the Romero Family. Today, the Grupo Romero is the leading Mexican egg producer. The development of this family company into a vertically integrated agrobusiness firm is briefly described in this article. The expansion of the poultry industry has changed the agricultural structure of the Valley of Tehuacan consider ably. However, this process has occurred in a relatively isolated way, so that traditional farming has only been affected to a small extent. At present, the chicken output capacity in the study area amounts to nearly 40 million. Several maps illustrate this development from the sixties up to 1984.